Using the National Aeronautics Space Administration Task Load Index (NASA-TLX) in surgery: Considerations for use "in the wild". (September 2022) - Zamudio, Jennifer; Catchpole, Ken; Kanji, Falisha; Anger, Jennifer; Cohen, Tara
Despite a variety of attempts to infer measurements of workload through more objective means, the NASATLX remains the most preferred tool in various industries. Interest in patient safety and healthcare systems design has seen a frequent application of the NASA-TLX over other methods within a range of surgical settings and has generated other adaptations to increase its sensitivity to specific tasks. However, in moving out of simulation settings and into real-world surgical settings, there are a range of challenges that need to be considered and addressed that have not been regularly reported in literature assessing intraoperative workload. In this paper, we offer insights from both prior research and our own studies that illustrate the value of using the NASA-TLX, and the potential pitfalls, to understand workload in surgery.